Politik Hukum Pengaturan Kampanye Berbasis Keadilan dalam Pemilihan Umum di Indonesia - Amin, Fakhry; Ester Hayatulah, Getah (Fakultas Hukum, Universitas Islam Balitar, 2024)
General elections in Indonesia as a pillar of democracy, view political campaigns as the main means of introducing candidates and political parties. However, campaigns must be based on the principles of justice and fair law to maintain the integrity of democracy. Major challenges arise in maintaining campaign fairness, especially regarding campaign fund transparency. This research uses normative legal methods by analyzing legal norms related to campaigns in general elections. The results show that laws and regulations, such as Law No. 7/2017 on General Elections and KPU Regulation No. 23/2018, aim to maintain fairness in political campaigns, although there are still implementation barriers, such as unequal access to resources, lack of transparency in campaign fund arrangements, and uneven media access. The issue of spreading false information or hoaxes is also a concern in political campaigns.